2005
DOI: 10.1007/s00018-005-4522-8
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-actin interactions

Abstract: The integrin family of extracellular matrix receptors regulates many aspects of cell life, in particular cell adhesion and migration. These two processes depend on organization of the actin cytoskeleton into adhesive and protrusive organelles in response to extracellular signals. Integrins are important switch points for the spatiotemporal control of actin-based motility in higher eukaryotes. Ligands of integrin cytoplasmic tails are central elements of signalling pathways involving small GTPases as well as pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(120 citation statements)
references
References 266 publications
2
117
0
1
Order By: Relevance
“…S5) (10). Integrins drive changes in cell shape by affecting the actin cytoskeleton (21). Accordingly, we found that internal perfusion of the actin polymerizing inhibitor latrunculin A (latA, 0.1 M) delivered through the patch pipette eliminated MMP-9-induced spine expansion and synaptic potentiation (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…S5) (10). Integrins drive changes in cell shape by affecting the actin cytoskeleton (21). Accordingly, we found that internal perfusion of the actin polymerizing inhibitor latrunculin A (latA, 0.1 M) delivered through the patch pipette eliminated MMP-9-induced spine expansion and synaptic potentiation (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…5 The direct partner of CAP1 is likely to be Talin because CAP1 interacts with Talin in yeast two-hybrid screens. 37 Talin is a cytoskeletal protein that is also a component of focal adhesion complexes, 38 providing a physical link between integrins and the cytoskeleton by binding to the cytoplasmic portion of integrin. During cell adhesion, it induces conformational changes in integrin extracellular domains that result in increased affinity for ligands.…”
Section: Cap1 Depletion Likely Activates Integrin Pathway Through Insmentioning
confidence: 99%
“…These proteins have been shown to have a central role in modulating integrin-dependent cell behaviors, including cell adhesion, migration and spreading. 54 Aberrant Rho GTPases signalling has, therefore, a profound impact on various aspects of cancer pathophysiology. Importantly, CD151 overexpression was found to activate Rac, Cdc42, but not Rho in A431 epidermoid carcinoma cells.…”
Section: Modulation Of Integrin-ligand Interactionsmentioning
confidence: 99%